Safety and Efficacy Using the Second-Generation Cryoballoon in Patients With Atrial Fibrillation and a Common Ostium of Inferior Pulmonary Veins - Xie, Hai-yang; Guo, Xiao-gang; Yang, Jian-du; Li, Jia-hui; Chen, Yan-qiao; Cao, Zhong-jing; Sun, Qi; Li, Xiao-yao; Ma, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Common ostium of inferior pulmonary veins (COIPV) is a kind of pulmonary vein variation. The safety and efficacy of COIPV isolation using the second-generation cryoballoon (CB) ablation remain unknown. Methods: A total of 10 patients with COIPV from a consecutive series of 1,751 patients with atrial fibrillation (AF) were included. Pulmonary vein isolation (PVI) was performed using the second-generation CB. Results: The prevalence of a COIPV was 0.57% in this study. PVI was achieved in all pulmonary veins (PVs) without the need for a touch-up. A segmental freeze strategy was applied for each inferior PV, respectively. The mean number of freeze cycles of inferior PVs was 1.4 ± 0.5 for the left inferior pulmonary vein (LIPV), and 2.0 ± 0.9 for the right inferior pulmonary vein (RIPV). Pulmonary vein potential (PVP) of RIPV could not be monitored in real-time in three cases. Eight of 10 patients (80%) were free from atrial arrhythmias without the use of antiarrhythmic drugs during a follow-up period of 23.6 ± 12.9 months. No procedure-related complications occurred in any of the 10 patients. Conclusions: Common ostium of inferior pulmonary veins is a rare but challenging PV variant. PVI with this unusual anatomic variation using the second-generation 28-mm CB is effective and safe.